Beispiel Nr: 33
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y=-\frac{1}{2}x^2+2x+5\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y=-\frac{1}{2}x^2+2x+5\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-\frac{1}{2}x^2+2x+5 \\ y=-\frac{1}{2}(x^2-4x-10) \\ y=-\frac{1}{2}(x^2-4x+2^2-2^2-10) \\ y=-\frac{1}{2}[(x-2)^2-2^2-10] \\ y=-\frac{1}{2}[(x-2)^2-4-10] \\ y=-\frac{1}{2}[(x-2)^2-14] \\ y=-\frac{1}{2}(x-2)^2+7 \\ Scheitel(2/7) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-\frac{1}{2}x^2+2x+5 \\ y=-\frac{1}{2}(x^2-4x)+5 \\ y=-\frac{1}{2}(x^2-4x+2^2-2^2)+5 \\ y=-\frac{1}{2}[(x-2)^2-2^2]+5 \\ y=-\frac{1}{2}[(x-2)^2-4]+5 \\ y=-\frac{1}{2}(x-2)^2+2+5 \\ y=-\frac{1}{2}(x-2)^2+7 \\ Scheitel(2/7) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=-\frac{1}{2}x^2+2x+5 \\ xs=-\frac{2}{2\cdot \left(-\frac{1}{2}\right)} \\ xs=2 \\ ys=5-\frac{2^2}{4\cdot\left(-\frac{1}{2}\right)} \\ ys=7 \\ Scheitel(2/7)\\ y=-\frac{1}{2}(x-2)^2+7 \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = ]-\infty;7]\\ \\=-\frac{1}{2}(x+1,74)(x-5,74)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y=-\frac{1}{2}x^2+2x+5 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -\frac{1}{2}x^{2}+2x+5 =0 \\ x_{1/2}=\displaystyle\frac{-2 \pm\sqrt{2^{2}-4\cdot \left(-\frac{1}{2}\right) \cdot 5}}{2\cdot\left(-\frac{1}{2}\right)} \\ x_{1/2}=\displaystyle \frac{-2 \pm\sqrt{14}}{-1} \\ x_{1/2}=\displaystyle \frac{-2 \pm3,74}{-1} \\ x_{1}=\displaystyle \frac{-2 +3,74}{-1} \qquad x_{2}=\displaystyle \frac{-2 -3,74}{-1} \\ x_{1}=-1,74 \qquad x_{2}=5,74 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -\frac{1}{2}x^{2}+2x+5 =0 \qquad /:-\frac{1}{2} \\ x^{2}-4x-10 =0 \\ x_{1/2}=\displaystyle -\frac{-4}{2}\pm\sqrt{\left(\frac{\left(-4\right)}{2}\right)^2- \left(-10\right)} \\ x_{1/2}=\displaystyle 2\pm\sqrt{14} \\ x_{1/2}=\displaystyle 2\pm3,74 \\ x_{1}=5,74 \qquad x_{2}=-1,74 \end{array}\\ \end{array}\\ \underline{x_1=-1,74; \quad1\text{-fache Nullstelle}} \\\underline{x_2=5,74; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-1,74&< x <&5,74&< x\\ \hline f(x)&-&0&+&0&-\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-1,74;5,74[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-\infty;-1,74[\quad \cup \quad]5,74;\infty[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$